1999
DOI: 10.1046/j.1365-2648.1999.00863.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing acute psychiatric patients: a quantitative and qualitative study

Abstract: Political and managerial attention has focused on the consequences of the failure of community services to provide effective care to a small number of people with severe mental illness. However, the nature and value of care in hospitals have received less scrutiny. This paper addresses deficiencies in our knowledge about nursing care in acute psychiatric wards. It reports the findings from a recently completed study for the United Kingdom Department of Health. Four key developments are identified which, togeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
81
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 29 publications
(22 reference statements)
0
81
2
Order By: Relevance
“…Low activity and social engagement for patients have remained stable in recent years and limited nursing time is spent in direct contact with patients (Sandford et al, 1990;Sanson-Fisher et al, 1979) and even less providing therapeutic activities (Bee et al, 2006;Whittington and McLaughlin, 2000;Ryrie et al, 1998). Furthermore, it has been shown that higher grade nurses spend less of their time directly with patients (Higgins et al, 1999;Cormack et al, 1976;Bee et al, 2006).…”
Section: Psychiatrymentioning
confidence: 99%
“…Low activity and social engagement for patients have remained stable in recent years and limited nursing time is spent in direct contact with patients (Sandford et al, 1990;Sanson-Fisher et al, 1979) and even less providing therapeutic activities (Bee et al, 2006;Whittington and McLaughlin, 2000;Ryrie et al, 1998). Furthermore, it has been shown that higher grade nurses spend less of their time directly with patients (Higgins et al, 1999;Cormack et al, 1976;Bee et al, 2006).…”
Section: Psychiatrymentioning
confidence: 99%
“…The question that arises, then, is, what effect a heavier workload that includes processing admissions, discharges, and transfers has on nurse-client interactions? What is known is that nurses have reported that the lack of resources such as secretarial support increased their administrative workload, resulting in a decreased amount of time available for nurseclient interactions (Cleary, 2004;Cleary & Edwards, 1999;Fourie et al, 2005;Higgins et al, 1999). This is unfortunate as the essential element to the therapeutic process is the therapeutic relationship.…”
Section: Discussionmentioning
confidence: 92%
“…High patient turnover contributes to increased workload and negatively impacts patient outcomes and nurse satisfaction (Committee on the Work Environment for Nurses & Patient Safety Board on Health Care Services, 2004;Hickam et al, 2003). Psychiatric nurses have reported performing unnecessary routines including completing paperwork for personnel and billing and making duplicative documentation (Higgins, Hurst, & Wistow, 1999). Further, the lack of resources such as secretarial support increased nurses' administrative workloads, resulting in a decreased amount of time available for nurse-client interactions (Cleary, 2004;Cleary & Edwards, 1999;Fourie, McDonald, Connor, & Barlett, 2005;Higgins et al, 1999).…”
Section: Activity and Workload On An Inpatient Psychiatric Unitmentioning
confidence: 99%
“…Other nurses reported that they did not feel safe in their work environment (Poster & Ryan, 1994;Sammut, 1997). Furthermore, the lack of other types of resources such as secretarial support increased nurses' administrative workload resulting in a decreased amount of time available for nurse-client interactions (Cleary, 2004;Cleary & Edwards, 1999;Fourie et al, 2005;Higgins et al, 1999). In sum, staffing is a critical factor that can potentially influence the outcome of a physical restraint episode.…”
Section: Nurse Practice Environmentmentioning
confidence: 94%
“…The extant literature related to inpatient psychiatric nurses was conducted in Australia and New Zealand (Berg & Hallberg, 2000;Cleary, 2004;Cleary & Edwards, 1999;Delaney, Clearly, Jordan, & Horsfall, 2001;Farrell & Dares, 1999;Fourie, McDonald, Connor, & Barlett, 2005;Happell, Martin, & Pinikahana, 2003;O'Brien & Cole, 2004;Taylor & Barling, 2004), Canada (Robinson, Clements, & Land, 2003), England (Callaghan, 1991;Fagin, Brown, Bartlett, Leary, & Carson, 1995;Fagin et al, 1996;Hall, 2004;Higgins, Hurst, & Wistow, 1999;Mistral, Hall, & McKee, 2002;Sammut, 1997;Sullivan, 1993;Whittington, 2002;Whittington & Wykes, 1992), Norway (Severinsson & Hummelvoll, 2001), Sweden (Severinsson & Hallberg, 1998), Japan (Ito, Eisen, Sederer, Yamada, & Tachimori, 2001), and a combination of two or more of the above countries (Melchior, Bours, Schmitz, & Wittich, 1997;Thomsen, Arnetz, Nolan, Soares, & Dallender, 1999).…”
Section: Nurse Practice Environmentmentioning
confidence: 98%